Building an Environment That Motivates Education Sustainability in Tumbang Habaon Village, Gunung Mas, Central Kalimantan Province, During Pandemic through Participatory Action Research between Parents, Schools and Church - Silvia Rahmelia; Prasetiawati; Oktani Haloho; Fernando Dorothius Pongoh; Bambang Purwantoro (Asosiasi Dosen Pengembang Masyarajat (ADPEMAS) Forum Komunikasi Dosen Peneliti, 2022)
An environment that does not motivate the sustainability of education is a central issue in Tumbang Habaon Village, Tewah District, Gunung Mas Regency. This issue is illustrated by the weak motivation of students to come to school to study, the lack of parental guidance for school-age children and the school's not being optimal in conducting effective learning for students, especially during the pandemic. This community cervice of Christian Religious Education Study Program aims to empower education sustainability through Participatory Action Research (PAR) approach between parents, schools and also church. The problems were found then designed in several action plan including 1) Parent’s role in fostering student motivation to continue their education through parenting seminar; 2) Fostering the motivation of Junior High School (SMPN 4 Tewah) to learn and directing them to have goals in their education process through “Kelas Inspirasi” activities; 3) Train teachers of SMPN 4 Tewah in Tumbang Habaon to be able to evaluate effective learning and have implications for student learning development through K’13 Assessment Instruments Training; 4) Christian Education in GKE Kapania Congregation in Tumbang Habaon as an effort to urge residents about the importance of education through Sunday School (SHM) and Youth Service (SPRP). Participatory Action Research which has been done, were carried out between parents, students, congregation members and stake holder in Tumbang Habaon had a new perspective on the importance of education for children’s future and also collaborative motivation between parents, schools and the community to support the sustainability of education for the children in Tumbang Habaon